Model Pendampingan Komunikasi Antarpribadi Petugas Pembinaan Lapas Kelas IIB Kuala Simpang dalam Pembinaan Perilaku Narapidana Kasus Pembunuhan - Tashya Holillah (MUKASI: Jurnal Ilmu Komunikasi, 2022)
The Objective of the research is to analyze communiaction accompaniment model among the wardens of class IIB Prison, Kuala Simpang in developing homicidal prisoners. The Research uses constructive paradigm in which the phenomena are constructed objectively and scientifically. It also uses qualitative method, and the data are gathered by conducting library research, non-participant observation adan interview. The research subjects are the wardens, taken by using purposive sampling technique with criteria of those who accompanied homicidal prisoners. The result pf the research shows that the wardens used some models: social interaction model, behavioral counseling model, humanistic personal model and equality model. The form of inter-personal communication development. In this case, there are some obstructions- behavioral obstruction, physical obstruction, decoding obstruction, adan media obstruction, they can be solved by increasing facility and infrastructure which supported the process of accompaniment in devoloping homicidal prisoners in the class IIB Prisons, Kuala Simpang.